Shear Bond Strength of Resin Bonded to Bleached Enamel Using Different Modified 35% Hydrogen Peroxides - Moosavi H; Hajizadeh H; Shaykhvasy M (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Bleaching systems with different concentrations and applications are widely used to improve the visual appearance of the teeth, but one of the complications of these materials is reduction of bond strength for immediately bonding to the bleached enamel. Objectives: The aim of this study was to evaluate the influence of using different modified hydrogen peroxide bleaching agents on the shear bond strength of composite resin bonded to the bleached enamel. Materials and Methods: Forty-eight sound extracted premolar teeth were collected, sectioned 1 mm below the CEJ to detach the root. The proximal surfaces of the teeth were flattened using diamond disks and silicon carbide papers to achieve flat homogeneous enamel surfaces without exposure to the dentin. The teeth were randomly divided into four groups as follows (n = 12): group 1: bleaching with 35% hydrogen peroxide gel; group 2: bleaching with 35% hydrogen peroxide gel contained (casein phosphopeptide-amorphous calcium phosphate (CPP-ACP); group 3: bleaching with 35% hydrogen peroxide gel combined with fluoride; and group 4: bleaching with 35% hydrogen peroxide applying one week before resin restoration placement. Composite resin, Clearfil AP-X (Kuraray, Tokyo, Japan), was bonded on each tooth in the mould (4 mm diameter × 3 mm height) using Clearfil SE Bond (Kuraray, Tokyo, Japan). After 24 hours of storage and 1000 cycles of thermocycling, the shear bond strength of the specimens at a cross-head speed of 0.5 mm/min was measured in MPa. Data were analyzed using ANOVA and Tukey's post-hoc test. Results: The minimum and maximum mean shear bond strength values were observed in groups 2 (15.82 ± 4.41) and 4 (21.00 ± 3.90), respectively. Multiple comparisons of groups revealed no significant differences among the groups except between group 4 and all the other groups. The most common type of failure was adhesive. Conclusions: Using modified bleaching agents decreased the bond strength of the composite resin to the enamel when it was used immediately after bleaching.